Glorify God with Your Body: An Exegesis on 1 Corinthians 6:12-20 and Its Implication for the Christian Life during Pandemic Covid-19 - Yesaya Adhi Widjaya (Diligentia: Journal of Theology and Christian Education, 2021)
In the current situation of life which is very difficult because of the pandemic Covid-19 and its consequences, the urgency for Christian to live holy is inevitable. The complexity and the problem of life were also evidence in 1st Corinthians. However, the attempt to exegete the certain passage of 1st Corinthians related to the current situation and considered the 1st Corinthians text as an encouragement for Christians to glorify God with our body has not yet been enough. Thus, it is prominent to ask the question as how Christian should live in this live with their body? This article aims to exegete 1st Corinthians 6:12-20 and demonstrate that this passage will in truly encourage every Christian to glorify God with their body in this difficult time. The first step is to translate the text directly from the Greek text. The second step is to demonstrate the structure and the exegesis of the text by analysing the grammar with its historical context. The third step which is parallel to the second step is to figure out the theological principles and their practical exhortation. The last step is the conclusion of this research and the application for the current life context. This research will employ the literature study by examine the commentary and journal articles which are relevant to the theme.